2008
DOI: 10.1099/ijs.0.65463-0
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus uvarum sp. nov., an uniseriate black Aspergillus species isolated from grapes in Europe

Abstract: A novel species, Aspergillus uvarum sp. nov., is described within Aspergillus section Nigri. This species can be distinguished from other black aspergilli based on internal transcribed spacers (ITS), b-tubulin and calmodulin gene sequences, by AFLP analysis and by extrolite profiles. Aspergillus uvarum sp. nov. isolates produced secalonic acid, common to other Aspergillus japonicus-related taxa, and geodin, erdin and dihydrogeodin, which are not produced by any other black aspergilli. None of the isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 28 publications
4
53
1
2
Order By: Relevance
“…These results are in agreement with previous findings reported by Perrone et al (2008) and Soni et al (2010) who found that filamentous fungi particularly Aspergillus and Trichoderma spp. are well known efficient producers of cellulases.…”
Section: Optimization Of Culture Conditions For Production Of Cellulasesupporting
confidence: 83%
“…These results are in agreement with previous findings reported by Perrone et al (2008) and Soni et al (2010) who found that filamentous fungi particularly Aspergillus and Trichoderma spp. are well known efficient producers of cellulases.…”
Section: Optimization Of Culture Conditions For Production Of Cellulasesupporting
confidence: 83%
“…In general, black Aspergillus species can be distinguished via a polyphasic approach, using morphology, physiology and molecular data (Samson et al, 2007); nevertheless, most of the species belonging to Aspergillus section Nigri are usually considered as A. niger based on only morphological characters (Martínez-Culebras & Ramon, 2007 Recently, clinical isolates thought to belong to A. niger have been reclassified by genetic tools as A. tubingensis, A. awamori, A. uvarum and A. brasiliensis (Perrone et al, 2008;Manikandan et al, 2010;Hendrickx et al, 2012;Szigeti et al, 2012). Accordingly, A. niger is not the only black Aspergillus species involved in infections, Indeed A. tubingensis and other black Aspergillus species are also able to cause infections.…”
Section: Black Aspergillus Species Isolated From Clinical and Environmentioning
confidence: 99%
“…Recently, the Aspergillus ''uniseriate'' population from grapes in Europe was characterized molecularly as a population quite different from A. japonicus and A. aculeatus (Perrone et al 2006b). This population is being described as a new species to be called A. uvarum (Perrone et al 2007d).…”
Section: Introductionmentioning
confidence: 99%